Highly Active and Stable Ordered Pt2feni/C Electrocatalyst for Oxygen Reduction Reaction: A Local Structural Investigation - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier B.V., 2025)
This research outlines the creation of a carbon-supported ordered platinum-iron-nickel (Pt2FeNi) ternary alloy electrocatalyst through a one-pot molten salt-assisted technique to tackle the slow kinetics of the oxygen reduction reaction (ORR). Transmission electron microscopy and X-ray diffraction confirmed the ordered face-centered tetragonal (fct) structure of S-Pt2FeNi/C, showing an average particle size of about 7 nm. X-ray photoelectron spectroscopy (XPS) demonstrated enhanced electrocatalytic performance and durability over time, attributed to variations in the Pt electronic structure caused by the existence of Fe and Ni atoms. An in-depth examination utilizing X-ray absorption spectroscopy revealed that S-Pt2FeNi/C displayed enhanced ORR activity than Pt/C, due to changes in the unoccupied d states of Pt atoms. The electrocatalysts (Pt2FeNi/C) showed remarkable stability, with improvements in electrochemical surface area, mass activity, and specific activity even after undergoing 30,000 potential cycles. The S-Pt2FeNi/C exhibited mass and specific activities that were 5.9 and 5.2 times greater than Pt/C, respectively. This innovative synthetic method holds potential for large-scale production of multimetallic ternary alloys directly on supporting materials, potentially reducing activity loss in PEMFCs (polymer electrolyte membrane fuel cells). © 2025 Elsevier B.V.